Determination the Toxicity of Poly Aromatic Hydrocarbons Using HPLC in Diyala River Sediments - Jasim, Hadi Hassan; Sultan, Muntadhar Salih (Al-Nahrain Journal of Science, 2018)
In this paper sixteen Polycyclic Aromatic Hydrocarbons (PAHs) are estimated in sediments in five locations along Diyala River where entering Baghdad city until flows into Tigris River, (PAHs) are organic compounds that contain two or more fused rings. Some of these compounds are classified as carcinogenic and mutagenic pollutants. Soxhlet technique is used in this work to extract PAHs from sediment samples with using methylene chloride as extraction solvent. High Performance Liquid Chromatography (HPLC) with UV-Vis detector is used for determination of PAHs. According to the results the maximum of total PAHs concentration in the sediment are found in the location No. 4 with1213.02mg/kg in summer and 283.17 mg/kg in winter, while the minimum of total PAHs concentration are found in location No. 1 with 46.42 mg/kg in summer and 16.70 mg/kg in winter. Locations numbers two three and five record values of total PAHs concentration with (148.35, 570.41 and 958.20 mg/kg) respectively in summer and (55.69, 100.47 and 171.55 mg/kg) respectively in winter. Naphthalene, Fluorene, Anthracene and Fluoranthene are the most dominant compounds in summer, while Benzo [k] fluoranthene, Benzo [a] pyrene, Benzo [ghi] perylene, Dibenz [a,h] anthracene and Indino [123cd] pyreneare the least compounds presence in all sites.